2016
DOI: 10.1186/s12940-016-0198-9
|View full text |Cite
|
Sign up to set email alerts
|

Portable air cleaners should be at the forefront of the public health response to landscape fire smoke

Abstract: Landscape fires can produce large quantities of smoke that degrade air quality in both remote and urban communities. Smoke from these fires is a complex mixture of fine particulate matter and gases, exposure to which is associated with increased respiratory and cardiovascular morbidity and mortality. The public health response to short-lived smoke events typically advises people to remain indoors with windows and doors closed, but does not emphasize the use of portable air cleaners (PAC) to create private or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 20 publications
1
41
0
2
Order By: Relevance
“…This epidemiologic evidence helps strengthen the association between wildfire smoke exposure and cardiovascular disease outcomes and highlights the increased risk to the older population. These findings, along with others, support the need for clinical research to assess the clinical and public health value of interventions to decrease exposure to particulate matter, and particularly to wildfire smoke, among those at highest risk 11, 12, 55, 57, 58, 59. As wildfire season intensity and duration is projected to increase in California, understanding adverse health impacts of wildfire smoke and identifying the most susceptible populations is relevant to a broad group of stakeholders, including state and local officials responsible for land and air quality management, environmental scientists, policy makers, public health officials, and frontline public health and healthcare practitioners.…”
Section: Discussionsupporting
confidence: 65%
“…This epidemiologic evidence helps strengthen the association between wildfire smoke exposure and cardiovascular disease outcomes and highlights the increased risk to the older population. These findings, along with others, support the need for clinical research to assess the clinical and public health value of interventions to decrease exposure to particulate matter, and particularly to wildfire smoke, among those at highest risk 11, 12, 55, 57, 58, 59. As wildfire season intensity and duration is projected to increase in California, understanding adverse health impacts of wildfire smoke and identifying the most susceptible populations is relevant to a broad group of stakeholders, including state and local officials responsible for land and air quality management, environmental scientists, policy makers, public health officials, and frontline public health and healthcare practitioners.…”
Section: Discussionsupporting
confidence: 65%
“…While recommending interventions to limit exposure to wildland fire smoke is prudent, particularly among those at highest risk, studies are needed to evaluate the benefits of such interventions. Considering the available data portable air filters have been advocated as a public health response to wildfire smoke (Barn et al, 2016). Fisk and Chan (Fisk and Chan, 2016) further advanced this concept by estimating the health benefits expected of in-home interventions that improve the quality of the indoor air during wildfires.…”
Section: Public Health Guidance and Interventionsmentioning
confidence: 99%
“…Outdoor PM 2.5 can infiltrate indoors in buildings even with closed windows and merely staying indoors provides limited protection against outdoor PM [20]. Many past studies have concluded that wildfire PM 2.5 are important sources of adverse respiratory health outcomes [21,22,23] and staying indoors combined with the use of air cleaners can effectively reduce PM 2.5 exposure during wildfire seasons [19,24,25,26]. In many communities, the use of air cleaning technology is often overlooked due to cost and a lack of information.…”
Section: Introductionmentioning
confidence: 99%